The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.amepre.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and BMI Trajectory: The Mediating Role of Depression

Abstract: Introduction Childhood maltreatment is associated with later obesity, but the underlying mechanisms are unknown. The objective of this study was to estimate the extent to which depression mediates the associations between childhood maltreatment and BMI in adolescence through adulthood. Methods Data on a cohort of 13,362 adolescents in the National Longitudinal Study of Adolescent to Adult Health (Wave I [1994–1995] to Wave IV [2008–2009]) were analyzed in 2015–2016. Classes of maltreatment experienced prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
2
17
0
1
Order By: Relevance
“…Com isso, considera-se que os indivíduos que estão com IMC elevado tendem a ter maior nível de depressão. Esses resultados apoiam os achados de Antoniou, Bongers e Jansen (2017) e Sacks et al (2017).…”
Section: O Corpo E a Depressãounclassified
“…Com isso, considera-se que os indivíduos que estão com IMC elevado tendem a ter maior nível de depressão. Esses resultados apoiam os achados de Antoniou, Bongers e Jansen (2017) e Sacks et al (2017).…”
Section: O Corpo E a Depressãounclassified
“…Associations between cholesterol levels and psychological conditions have been a focus of interest ever since Engelberg (1992) hypothesized a link between serum lipid concentrations, depression, and suicidality. Many studies have focused on the associations between cholesterol levels and depression (Maes et al, 1997;Lehto et al, 2008;Lehto et al, 2010;Persons and Fiedorowicz, 2016) and also on the link between depression and ACEs (Dias de Mattos Souza et al, 2016;McCarthy-Jones and McCarthy-Jones, 2014;Rohde et al, 2008;Sacks et al, 2017;Tunnard et al, 2014). Altered levels of circulating lipids have been observed in adults who report ACEs compared to those with no such experiences (Groër et al, 2016;Lodhia et al, 2015).…”
mentioning
confidence: 99%
“…The relation between childhood maltreatment and overweight has been confirmed by two meta-analyses including 190,285 and 112,708 participants, respectively (12,13). Longitudinal studies with several assessments have shown that maltreatment is related to accelerated weight gain (14)(15)(16)(17), but report conflicting results with regard to which type of maltreatment drives this effect.…”
Section: Introductionmentioning
confidence: 92%
“…One study investigated posttraumatic stress disorder as a potential mechanism but only found a weak mediation effect (27). Another study found that depression fully mediated the association between physical abuse and BMI in girls but not in boys and did not play a role for other types of maltreatment (17). An alternative approach would be to focus on biological factors such as stress physiology.…”
Section: Introductionmentioning
confidence: 99%